TO ASSES THE FACTORS INFLUENCING THE STATE OF NUTRITION CARE IN THE INPATIENT THERAPEUTIC UNIT AT HOIMA REGIONAL REFERAL HOSPITAL IN UGANDA. - Komugisa, Allan; Okot Musoga, Ribon (Student's Journal of Health Research Africa, 2023)
Aim: The study was conducted to assess the factors influencing the state of nutrition care in the Inpatient Therapeutic Unit of Hoima Regional Referral Hospital. Methods: The study design used was a cross-sectional and retrospective study. Random sampling was used to select the participants. A questionnaire was used to draw data which was analyzed in Excel, and means, percentages, graphs, and charts were extracted. Results: The unit had 15 staff members, mostly (60%) female, and had no doctor. The staff members were mainly (33%) nurses and (13%) nutritionists. Most of the caretakers (93%) were females and were mainly peasants, single mothers and primary school drops 93%, 64%, and 57% respectively. Fevers (93%) and cough (64%) were the leading complaints, affecting (93%) and (64%) of the patients respectively. Septicaemia (79%) and malaria (50%) were the most common comorbidities, affecting 79% and 50% of the patients, respectively. Conclusions: The study established that knowledge, attitude, and practices had a great influence on the state of nutrition care in the in-patient therapeutic unit. It was also recognized that comorbidities had a significant influence on the treatment outcome of the patients. Nutrition care remained multi-dimension, requiring multi-stakeholder approaches. Recommendations: Establish a functional multi-stakeholder Quality Improvement Committee (QIC) to guide the operations of the unit.